Three new entomopathogenic fungal species isolated from soil in China - Liu, Tongyi; Chen, Wei; Zhang, Ke; Hu, Xiangyu; Berestetskiy, Alexander; Hu, Qiongbo; Weng, Qunfang (Frontiers in Microbiology, 2025)
Entomopathogenic fungi play a crucial role in integrated pest management by targeting pests through specific infection mechanisms, offering both environmental compatibility and sustainability. In recent years, the growing challenge of pesticide resistance and the increasing demand for green agriculture have made the exploration of novel entomopathogenic fungal resources a major research focus in biological control. In this study, we employed a combination of traditional morphological characterization and multi-locus phylogenetic analyses to identify and describe three new species: Gongronella yichunensis, Gongronella shangraoensis, and Yunnania jiujiangensis. For the genus Gongronella, the internal transcribed spacer (ITS) and rRNA large subunit (LSU) regions were used for phylogenetic reconstruction, while the genus Yunnania was analyzed using ITS, LSU, β-tubulin (β-TUB), and translation elongation factor (TEF) gene sequences. Furthermore, preliminary bioactivity assessments revealed varying levels of pathogenicity of the new species against Ostrinia furnacalis. Gongronella yichunensis (strain JX09A02) demonstrated the highest virulence, with a median lethal time (LT50) of 7.2 days and a median lethal concentration (LC50) of 28.0 × 106 spores/mL. Gongronella shangraoensis (strain JX20B02) exhibited intermediate efficacy, showing an LT50 of 8.4 days and an LC50 of 92.3 × 106 spores/mL. Yunnania jiujiangensis (strain JX11B02) displayed relatively lower virulence, with an LT50 of 9.5 days and an LC50 of 243.8 × 106 spores/mL. These findings not only enrich the genetic resources of entomopathogenic fungi in China but also provide a valuable theoretical and germplasm foundation for developing novel biocontrol agents.